ROOT CANAL TREATMENT IN CASE IRREVERSIBLE PULPITIS MAXILLARY PREMOLAR TEETH WITH DIRECT COMPOSITE: CASE REPORT - Christina Mahardika; Viona Sekar Melati (Indonesian Journal of Dentistry, 2025)
Background: Irreversible pulpitis is an inflammatory process in the tooth that involves the pulp. Teeth that experience inflammation in the pulp require root canal treatment to eliminate bacteria. Post root canal treatment teeth with minimal loss of healthy tissue can be restored with direct composite. The purpose of this case report is to convey the success of multiple root canal treatment in cases of irreversible pulpitis with direct restoration. Case: A 47-year-old female patient came to RSGM Unimus, complaining of frequent toothache when eating cold food and in the morning. Intraoral examination showed blackness on the cervical of tooth 14 with positive sondation. Radiographic examination showed radiolucency on the cervical buccal of tooth 14 with pulp depth.Conclusion: The treatment performed showed good results, with root canal treatment in cases of irreversible pulpitis and direct restoration, so that it can maintain teeth, prevent further infection, provide good aesthetics and provide satisfaction to patients.